Wednesday

August 20, 2014

August 20, 2014

Posted by **Jackster** on Monday, February 21, 2011 at 8:08pm.

-3x + 6y = -3 / -6x + 4y = -10

- algebra -
**Henry**, Tuesday, February 22, 2011 at 9:53pmEq1: -3X + 6Y = -3

Eq2: -6X + 4Y = -10

Multiply Eq1 by -2 and add the Eqs:

6X - 12Y = 6

-6X + 4Y = -10

Sum: -8Y = -4.

Y = 1/2.

Substitute 1/2 for Y IN Eq1

-3X + 3 = -3,

-3X = -6,

X = 2.

Solution Set = (2, 1/2).

**Related Questions**

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - solve using the elimination method. show your work. if the system has ...

Algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

Algebra - Solve using the elimination method. Show your work. If the system has ...

Algebra - Solve using the elimination method.Show work.If the system has no ...

intermediate algebra - Solve using the elimination method. Show your work. If ...